L'argent noir des syndicats - Gagnon, Mona-Josée (Relations industrielles / Industrial Relations, 2010)
The article reviews the book, "L'argent noir des syndicats," by Roger Lenglet, Jean-Luc Touly and Christophe Mongermont.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z